P–639 The role of chronic inflammation in polycystic ovarian syndrome – a systematic review and meta-analysis. (6th August 2021) - Amer, S; Aboeldalyl, S; Snell, L; Shawky, H; Seyam, E; Ibrahim, E
Abstract: Study question: Is polycystic ovarian syndrome (PCOS) associated with chronic inflammation as determined by elevated serum C-reactive protein (CRP) level independent of obesity? Summary answer: Circulating CRP is moderately elevated in women with PCOS (independent of obesity), which is indicative of low-grade chronic inflammation. What is known already: Although current literature associates polycystic ovarian syndrome (PCOS) with chronic inflammation, the evidence for this link remains inconclusive and its causal nature remains unclear. A systematic review and meta-analysis involving 31 studies was published on this topic in 2011 providing evidence for increased circulating CRP (96% higher than controls). However, since that review there have been over 100 published studies assessing CRP in PCOS women utilising more advanced CRP assays. Study design, size, duration: This systematic review involved an extensive search of electronic databases for studies investigating CRP and other inflammatory makers in PCOS women from January 2000 to March 2020. Searched databases included PUBMED, EMBASE and MEDLINE, SCOPUS, DynaMed plus, TRIP, ScienceDirect and Cochrane Library. Inclusion criteria were using Rotterdam criteria for PCOS diagnosis, measuring CRP with high-sensitivity assay, matching/adjusting participants for BMI, and including drug naïve participants who were free from conditions that could affect inflammatory markers. Participants/materials, setting, methods: The review included all studies comparing circulating CRP between women with and without PCOS. Articles' quality and risk of bias were assessed using modified Newcastle-Ottawa scale. CRP data were extracted from eligible studies and entered into RevMan software for calculation of standardized mean difference (SMD) and 95% Confidence Interval (CI). Sensitive analysis was performed for high-quality studies providing data for non-obese participants. Main results and the role of chance: The systematic review included 95 eligible studies (n = 10, 074), of which 68 (n = 7991) were included in a meta-analysis. Sixty-two of the 95 studies reported significantly higher circulating CRP in PCOS women (n = 5235) versus controls (n = 4839). The remaining studies showed no statistically significant differences between the two groups after adjusting for BMI. Pooled analysis of 68 studies revealed significantly higher circulating CRP in PCOS women (SMD 1.26, 95%CI, 1.01, 1.52; z = 9.60; p = 0.00001; I²=96%). Sensitivity meta-analysis for non-obese women in 37 high-quality studies showed significantly higher circulating CRP in PCOS women versus controls (SMD 1.84, 95%CI, 1.40, 2.28; z = 8.19; p < 0.00001; I²=97%). Circulating TNF- α was measured in 13 studies, of which seven reported higher levels in PCOS women versus controls and six showed no difference. Circulating IL–6 was measured in 19 articles, of which eight reported significantly higher levels in PCOS women versus controls and 11 found no difference. Four studies (n = 512) reported increased white cell count in PCOS women (n = 323) compared with healthy controls (n = 189). Nine studies (n = 922) assessed circulating adiponectin, with seven showing significantly lower levels in PCOS women (n = 368) versus controls and one showing no difference. Meta-analysis of four of these studies (n = 355) revealed a SMD –1.48 (95% CI; –2.48, -.14). Limitations, reasons for caution: High heterogeneity between studies and the small size of several studies are the main limitations. Heterogeneity is due to variation in laboratory methods used to measure CRP and variations between participants e.g. age, BMI and PCOS phenotypes. Sensitivity and sub-group analysis were performed to address this heterogeneity. Wider implications of the findings: Further research is required to understand the underlying molecular mechanisms and the pathophysiological role of chronic inflammation in PCOS. This could potentially identify targets for new treatments that could improve short- and long-term health problems associated with PCOS. Trial registration number: N/A